2022
DOI: 10.3390/ijms23031877
|View full text |Cite
|
Sign up to set email alerts
|

TLR4-Mediated Inflammatory Responses Regulate Exercise-Induced Molecular Adaptations in Mouse Skeletal Muscle

Abstract: Endurance exercise induces various adaptations that yield health benefits; however, the underlying molecular mechanism has not been fully elucidated. Given that it has recently been accepted that inflammatory responses are required for a specific muscle adaptation after exercise, this study investigated whether toll-like receptor (TLR) 4, a pattern recognition receptor that induces proinflammatory cytokines, is responsible for exercise-induced adaptations in mouse skeletal muscle. The TLR4 mutant (TLR4m) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Exploring regulation of gut permeability by GMB composition, we propose that exercise-induced increase in AMPK signaling may be a possible candidate for future research (Macinnis and Gibala, 2017) as AMPK signaling has been found to increase on a similar timeframe as exercised induced increases in gut permeability (Gibala et al, 2009). The connection between these systems may be through lipopolysaccharide (LPS, a biomarker of gut permeability) activation of skeletal muscle TLR4 receptors, resulting in downstream AMPK activation (Fujiyoshi et al, 2022). Preceding biologic events such as AMPK that trigger the cascade of exercise adaptation have so far been under-explored.…”
Section: Evidence Of Microbiome Composition Influencing Voluntary Exe...mentioning
confidence: 99%
“…Exploring regulation of gut permeability by GMB composition, we propose that exercise-induced increase in AMPK signaling may be a possible candidate for future research (Macinnis and Gibala, 2017) as AMPK signaling has been found to increase on a similar timeframe as exercised induced increases in gut permeability (Gibala et al, 2009). The connection between these systems may be through lipopolysaccharide (LPS, a biomarker of gut permeability) activation of skeletal muscle TLR4 receptors, resulting in downstream AMPK activation (Fujiyoshi et al, 2022). Preceding biologic events such as AMPK that trigger the cascade of exercise adaptation have so far been under-explored.…”
Section: Evidence Of Microbiome Composition Influencing Voluntary Exe...mentioning
confidence: 99%